The nature, extent and impact of educator targeted bullying on school teachers in West Malaysia - Santos, Angeli; Tin, Jia Jian (Taylor & Francis, 2016)
This study examines the nature, prevalence and impact of educator targeted bullying (ETB) in a sample of 575 Malaysian school teachers. Specifically it was predicted that ethnicity may be related to exposure to ETB; that frequency of exposure would vary by type of ETB; that there would be tenure-related differences in terms of exposure and burnout; and that teaching experience could moderate the exposure burnout relationship.